Entre la producción y el mercado: análisis de una experiencia agroecológica en Chocontá, Cundinamarca (2020)
The growing global food crises, apparently caused by a dysfunctional agri-food system, have sparked growing social concern about food and inequality food distribution. In response, several social and academic sectors have encouraged the adoption and dissemination of alternative agriculture proposals, such as agroecology, to counteract negative impacts at the social, economic and environmental levels. Although these alternative proposals have gained popularity in many parts of the world, some authors have drawn attention to the need for a a critical eye that allows understanding how they are operating in practice. This work answers that call and proposes an analysis of agroecology in the articulation of production with market requirements. Based on the Food regime theory of Philip McMichael and Harriet Friedmann, and the model of cultural economy of Jane Dixon, this work analyzes this articulation with the study of a particular case of a small peasant organization in Chocontá - Cundinamarca (ORC). This research deals with the difficulties faced by this organization and the possible aspects that make the proper operation of agroecology. It was sought to emphasize that the agroecological commitment is not limited to a mode of production but also to new forms of social organization, which generate new forms of relationships between the different actors in the food system. The misapplication of the integral model runs the risk of of a conventionalization in the relationship between marketing and production.